Transport management: The popularity of study programmes among the applicants to Lithuanian universities evaluating the qualifications of graduates in the labour‐market - Prentkovskis, Olegas; Kliukas, Romualdas; Vasiliauskas, Aidas V.; Daniūnas, Alfonsas; Marina, Valerija; Ledauskaitė, Kristina; Zemlickienė, Vaida (Transport, 2009)
The accession of Lithuania to the European Union made transport one of the most important branches of national economy. Presently, economic development is hardly possible without an efficient transport system (providing both local and international transportation). The operation of industrial, construction and agricultural enterprises as well as work efficiency and a public opinion largely depend on the reliability and effective performance of transport systems which is not possible without qualified transport managers. The paper presents requirements raised for controlling the abilities and level of educating specialists in Transport Management and introduces employee assesment at student skills. Specialists in Transport Management are trained at vocational and higher schools of Lithuania. Experts in the field of Transport Management are trained at two university‐level higher schools in Lithuania (Bachelors, Masters and Doctors) including Vilnius Gediminas Technical University and The General Jonas Žemaitis Military Academy of Lithuania (the introduced higher schools are located in Vilnius, the capital of Lithuania). Although both study programmes taught at the above mentioned higher schools cover the area of Transport Management, they have some differences discussed in the paper. A brief survey of admission to Lithuanian higher schools is analyzed in the article. Some statistical data on the popularity of study programmes chosen by the applicants participating in the joint admission programme to Lithuanian higher schools is presented in the article. Also the popularity of the study programmes of Transport Management (competition, competitiveness indices and average competitive marks and motivation indices) available at two higher schools of Lithuania is described. First published online: 27 Oct 2010